Re-testing liquidity constraints in ten Asian developing countries - Lee, Yuan-Ming; Wang, Kuan-Min (Uniwersytet Ekonomiczny we Wrocławiu, 2010)
This paper suggests that the strength or weakness of the economy can affect short-runconsumption and consumer borrowing in the credit markets, and that these behaviouralchanges are key factors determining liquidity constraints. A nonlinear threshold model isdeveloped, with the threshold variable of the real GDP growth dividing the model into tworegimes: strong economy and weak economy. The model is used to test again for liquidityconstraints on consumers in the ten Asian countries analyzed in Habibullah et al. (2006). Ofthe ten countries, seven are found to exhibit nonlinearity in their consumption data. Thisconfirms that levels of economic growth affect the proportion of consumers who are liquidityconstrained. Weak economic growth is found to be associated with higher levels of liquidityconstraints, and strong economic growth with lower levels of constraints.
Argumenta Oeconomica, 2010, Nr 2 (25), s. 25-50
Keywords: liquidity contrains; business cycle; treshold model; permanet income hypothesis